Understanding Robustness of Magnetically Driven Helical Propulsion in Viscous Fluids Using Sensitivity Analysis. Issue 4 (7th February 2022) - Venezian, Roberto; Khalil, Islam S. M.
Abstract: Magnetically‐actuated helical microrobots can propel themselves in fluids and tissues‐like mediums with a wide range of Reynolds numbers ( Re ). The properties of physiological fluids and input parameters vary in time and space and have a direct influence on their locomotion along prescribed paths. Therefore, understanding the response of microrobots to variations in rheological properties and input parameters become increasingly important to translate them into in vivo applications. Here, a physical framework is presented to understand and predict key parameters whose uncertainty affect certain state variables most. A six‐degree‐of‐freedom magneto‐hydrodynamic model is developed based on the resistive force theory (RFT) to predict the response of robots swimming through different fluids and examine their response during transitions into Newtonian–viscoelastic interfaces. Performance of the robot, while swimming in a fluid with a fixed viscosity, is quantified using sensitivity analysis based on the magneto‐hydrodynamic model. The numerical results show how abrupt changes in viscosity can affect their ability to rotate with the rotating field in synchrony. The sensitivity analysis shows that the states of the robot are mostly sensitive to variations in the actuation frequency. Open‐loop experiments are performed using a permanent‐magnet robotic system comprising a robotic arm and a rotating permanent magnet to actuate and control a helical robot at the Newtonian–Viscoelastic interface and validate the theoretical predictions of the RFT‐based sensitivity analysis. Abstract : Understanding the hydrodynamic response of microrobots to variations in rheological properties is essential to translate these devices into in vivo applications. A magneto‐hydrodynamic model and sensitivity analysis reveal how the states of the microrobots are selectively affected based on controlled changes in actuation and rheological properties of the environment. The motion of the helical robot between Newtonian and viscoelastic mediums is studied theoretically and experimentally using global sensitivity analysis.